ATM and ATR, two central players of the DNA damage response, are involved in the induction of systemic acquired resistance by extracellular DNA, but not the plant wound response - Vega-Muñoz, Isaac; Herrera-Estrella, Alfredo; Martínez-de la Vega, Octavio; Heil, Martin (Frontiers in Immunology, 2023)
Background: The plant immune response to DNA is highly self/nonself-specific. Self-DNA triggered stronger responses by early immune signals such as H2O2 formation than nonself-DNA from closely related plant species. Plants lack known DNA receptors. Therefore, we aimed to investigate whether a differential sensing of self-versus nonself DNA fragments as damage- versus pathogen-associated molecular patterns (DAMPs/PAMPs) or an activation of the DNA-damage response (DDR) represents the more promising framework to understand this phenomenon. Results: We treated Arabidopsis thaliana Col-0 plants with sonicated self-DNA from other individuals of the same ecotype, nonself-DNA from another A. thaliana ecotype, or nonself-DNA from broccoli. We observed a highly self/nonself-DNA-specific induction of H2O2 formation and of jasmonic acid (JA, the hormone controlling the wound response to chewing herbivores) and salicylic acid (SA, the hormone controlling systemic acquired resistance, SAR, to biotrophic pathogens). Mutant lines lacking ATAXIA TELANGIECTASIA MUTATED (ATM) or ATM AND RAD3-RELATED (ATR) – the two DDR master kinases – retained the differential induction of JA in response to DNA treatments but completely failed to induce H2O2 or SA . Moreover, we observed H2O2 formation in response to in situ-damaged self-DNA from plants that had been treated with bleomycin or SA or infected with virulent bacteria Pseudomonas syringae pv. tomato DC3000 or pv. glycinea carrying effector avrRpt2, but not to DNA from H2O2-treated plants or challenged with non-virulent P. syringae pv. glycinea lacking avrRpt2. Conclusions: We conclude that both ATM and ATR are required for the complete activation of the plant immune response to extracellular DNA whereas an as-yet unknown mechanism allows for the self/nonself-differential activation of the JA-dependent wound response.